Leading Change: Reproductive Rights, Empowerment and Feminist Solidarity in the Dublin Bay North Repeal the 8th Campaign - Antosik-Parsons, Kate (My University, 2022)
This article examines how the Dublin Bay North (DBN) Repeal the 8th activist group, an independent women-led, grassroots movement in the largest constituency in Ireland, practiced a collectivist approach to forms of ‘power-with’ and ‘power-to’ (Allen, 2018) that enabled the group to create an activist community based upon a feminist ethics of ‘caring-with’ (Tronto, 1993). In 2018 in Dublin, what had been a narrow majority in 1983 against abortion rights became a decisive 3:1 margin in favour. While this remarkable change can be attributed to the efforts of numerous feminist and reproductive rights activists working for many years, including those tied to the national Together for Yes campaign, less attention has been paid to new activist leaders participating at the grassroots level. This article focuses on the leadership roles adopted by first-time grassroots activists who became ‘team leaders’ and ran decentralised campaigns in their neighbourhoods. Using qualitative analyses of a survey of 125 members (June 2018), 16 semi-structured interviews with DBN team leaders and other key people within the campaign (October 2018 and March 2019), and the authors’ own experiences, we consider how new activists recruited and empowered others to tell their stories, canvass, and lead their own actions.
PUBLISHED
Keywords: Ireland, feminist activism, reproductive rights, empowerment, leadership; Inclusive Society; Making Ireland; Abortion; Human rights; SOCIAL POLICY; Social Movements; body politics and practices; Other; Advocacy and political participation; Gender